A case report of acute Marchiafava-Bignami disease: a rare clinical entity in chronic alcoholism (Medical Journal of Indonesia, 2021)
Marchiafava‑Bignami disease (MBD) is a rare neurological disease often associated with a chronic consumption of alcohol and malnutrition, which is characterized by a demyelination and necrosis of the corpus callosum. We present a case of a 21-year-old male with chronic alcoholism who presented with an acute altered sensorium and seizure, which were initially treated as meningoencephalitis. His persistent poor Glasgow coma scale score and ideomotor recovery with encephalitic changes on his electroencephalogram prompted urgent magnetic resonance imaging (MRI) of his brain, which revealed extensive symmetrical hyperintensities in the corpus callosum. The diagnosis of MBD was made because of the typical MRI findings and after the exclusion of other possible diagnosis. The patient was promptly treated with a parenteral thiamine and showed a good recovery at 3 months follow-up. This case highlights the importance of diagnosing and recognizing MBD in a patient with chronic alcoholism as prompt treatment could prevent irreversible damage, which could carry high morbidity.